2015
DOI: 10.1111/jre.12260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeic acid phenethyl ester on Prevotella intermedia lipopolysaccharide‐induced production of proinflammatory mediators in murine macrophages

Abstract: Modulation of host response by CAPE may represent an attractive strategy towards the treatment of periodontal disease. In vivo studies are required to appraise the potential of CAPE further as an immunomodulator in the treatment of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 57 publications
(77 reference statements)
3
19
0
Order By: Relevance
“…3 In preclinical models, CAPE protected against ligature-induced periodontitis 4 and systemic bone loss by cortisone, 5 and supported bone defect healing. 6 Therefore, CAPE is attracting attention in periodontology, 7,8 and interest is growing in uncovering the beneficial effects of CAPE in periodontal therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 In preclinical models, CAPE protected against ligature-induced periodontitis 4 and systemic bone loss by cortisone, 5 and supported bone defect healing. 6 Therefore, CAPE is attracting attention in periodontology, 7,8 and interest is growing in uncovering the beneficial effects of CAPE in periodontal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CAPE prevents damage of cells exposed to hydrogen peroxide, including neurite PC12 cells, 12 retinal 661W cells 13 and umbilical vein endothelial cells. 14 CAPE also exerts anti-inflammatory activity in gingival fibroblasts 7 and macrophages 8 exposed to endotoxins. Thus, CAPE supports the major defence mechanisms of cells challenged by oxidative stress and inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has indicated that different mechanisms are involved in the various functions of CAPE, including induction of HO-1 expression, activation of the ERK1/2-CREB signalling cascade and inhibition of NF-κB signals in different cell contexts and different disease models [ 42 45 ]. We found that CAPE upregulated the HIF-1α and SDF-1α gene and protein expression in BMECs, which further supports the hypothesis that CAPE has the ability to improve haematopoietic cell homing by regulating the BM niche (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeic acid phenethyl ester (CAPE) has antioxidant, antitumoral, anti-inflammatory, and immunomodulatory properties and inhibits ROS production during inflammatory processes [59]. Recently, it has been reported that CAPE can modulate the host response [60]. Yiğit et al [19] evaluated the effects of LDD and CAPE on alveolar bone level and the plasma levels of GSH-Px activity in an experimental periodontitis rat model.…”
Section: Glutathione Peroxidase Medication and Periodontal Diseasementioning
confidence: 99%